Determinants of Long-acting Reversible Contraception (LARC) Use among Women of Reproductive Age in Indonesia: 2017 IDHS Data Analysis - Lydia Kurniatin; Elma Marsita; Darojad Nurjono Agung Nugroho (Women, Midwives and Midwifery, 2023)
Background: The achievement of active Long-acting reversible contraceptive (LARC) participants for West Kalimantan Province was only 9.54% in 2019 and it has not meet with the main performance target in the Strategic Plan (2015-2019) 15.19%. Research Objectives: To analyze the determinants of the use of LARC by women of reproductive age in West Kalimantan based on the results of the 2017 IDHS data analysis. Research Method: Analytical research with cross-sectional research design and using data from the 2017 IDHS in West Kalimantan. The research sample was all women of reproductive age aged 15-49 years in West Kalimantan who were using contraception, namely 501 respondents. Results: Bivariate analysis illustrates that there is a correlation between age (p value = 0.008), education level (p value = 0.002), parity (p value = 0.009), place of residence (p value = 0.005, economic status (p value = 0.000), and internet access with the status of LARC usage by women of reproductive age in West Kalimantan (p value = 0.000). Other results concluded that there was no relationship between the variables  of work (p value = 0.3), knowledge (p value = 0.674), distance to health services (p value = 0.2 ), health promotion by health workers (p value = 0.478), spousal support (p value = 0.8) and the variable number of wanted children with the status of women of reproductive age using LARC in West Kalimantan (p value = 0.173). Conclusion: There is a need to increase education and reach of contraceptive services for husbands by conduction collaborative works with public figure, religious leaders and women's organizations in carrying out health promotions about contraception in various public facilities.